Kemajuan Terkini Bioplastik Berbasis Sagu: Metode Preparasi, Karakteristik, Tantangan, dan Perspektif Masa Depan - Rizky Fian Azhari; Susilowati Susilowati; Agnes Dyah Novitasari Lestari (Environmental Insight Journal, 2026)
The increasing use of petroleum-based plastics has led to various environmental problems due to their non-biodegradable nature. Therefore, the development of bioplastics derived from renewable resources has become a promising alternative, including sago-based bioplastics, which are abundant and have high starch content. This review article aims to examine recent advances in the preparation of sago-based bioplastics, their resulting properties, challenges in their development, and future application prospects. The method used in this study is a literature review of various relevant scientific articles related to the production and development of sago-based bioplastics. The findings indicate that the properties of sago-based bioplastics can be improved through formulation modification, the addition of plasticizers, reinforcement with fillers, and appropriate processing techniques. Sago-based bioplastics exhibit good biodegradability; however, they still face several limitations, such as low water resistance and mechanical properties that require further improvement. With advances in material modification technologies and formulation innovations, sago-based bioplastics have significant potential to become sustainable and environmentally friendly alternative materials.